Investigation of band alignment between InAlAs and atomic-layer-deposited HfO2/Al2O3 by X-ray photoelectron spectroscopy. (27th March 2019) - Wu, Li Fan; Miao, Rui Xia; Li, Yong Feng
Abstract: Band alignments between atomic layer deposition (ALD) HfO2 /Al2 O3 double layers and InAlAs were investigated by angle-resolved X-ray photoelectron spectroscopy (AR-XPS). The relationship of As and Hf 4f peaks reducing with the decreasing take-off angle θ indicated upward band bending on the InAlAs surface and a potential gradient in the HfO2 /Al2 O3 layer. AR-XPS measurements were combined with numerical calculations. The valence band and conduction band discontinuity between HfO2 /Al2 O3 and InAlAs were 2.49 ± 0.2 eV and 1.86 ± 0.2 eV, respectively. A low leakage current density of 7.01 × 10 −7  A cm −2 at 1 V and oxide trapped charge densities of 9.925 × 10 11  cm −2 were obtained.